An initial investigation into compensation processes for employees in the Ugandan industrial agriculture sector who acquire disabilities through accidents at work, 2015-2023 - Modern, Julia (UK Data Service, 2024)
The research that produced the data in this upload was initial scoping fieldwork looking at outcomes for people who become disabled through workplace accidents in the industrial agriculture sector in Uganda. The PI, Dr Julia Modern, spent six weeks in a Ugandan town and its surroundings, collecting initial data about how disabled survivors of accidents seek justice. This was an initial study to investigate the feasibility of following the progress of accident survivors’ cases through longer-term fieldwork. The research had four objectives: Two primary objectives: • Identify institutions with which accident survivors interact when attempting to elicit compensation or other forms of redress; • Identify key individuals who have been involved in collective action for survivors of accidents in the areas investigated. Two secondary objectives: • Identify rhetorical strategies used by different actors to argue for redress and how they relate to the outcomes of survivors’ campaigns; • Identify existing links between Organisations of People with Disabilities (OPDs) and individuals or groups of survivors of industrial plantation-related accidents. The research that produced the data in this upload was initial scoping fieldwork looking at outcomes for people who become disabled through workplace accidents in the industrial agriculture sector in Uganda. The PI, Dr Julia Modern, spent six weeks in a Ugandan town and its surroundings, collecting initial data about how disabled survivors of accidents seek justice. This was an initial study to investigate the feasibility of following the progress of accident survivors’ cases through longer-term fieldwork. The research had four objectives: Two primary objectives: • Identify institutions with which accident survivors interact when attempting to elicit compensation or other forms of redress; • Identify key individuals who have been involved in collective action for survivors of accidents in the areas investigated. Two secondary objectives: • Identify rhetorical strategies used by different actors to argue for redress and how they relate to the outcomes of survivors’ campaigns; • Identify existing links between Organisations of People with Disabilities (OPDs) and individuals or groups of survivors of industrial plantation-related accidents.